2021
DOI: 10.21037/atm-20-6456
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-derived miR-196b-5p facilitates intercellular interaction in infantile hemangioma via down-regulating CDKN1B

Abstract: Background: Though infantile hemangioma (IH) is a common benign vascular tumor, its pathogenesis remains unclear. This study explored the function of hemangioma-derived stem cells (HemSCs) derived exosomes, which exerted an intercellular effect on hemangioma-derived endothelial cells (HemECs).Methods: First, HemSCs and HemECs were extracted and cultured. HemSCs derived exosomes (HemSCsexos) were harvested. miRNA sequencing and target prediction were used to explore differentially expressed miRNAs and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Some mechanisms by which miR-196b-5p regulates gene expression have been known [ 34 36 ]. In our previous data, we discovered that METTL3 was differentially expressed in the miR-196b-5p knockdown group and Consh group by SWATH-MS array [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some mechanisms by which miR-196b-5p regulates gene expression have been known [ 34 36 ]. In our previous data, we discovered that METTL3 was differentially expressed in the miR-196b-5p knockdown group and Consh group by SWATH-MS array [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy‐six publications were found in this section, from Iran, Japan, China, Korea, and India, performed between 2013 and 2022. [ 127,174–248 ] Of these ncRNAs, 3 circRNAs, 14 lncRNAs, and 45 microRNAs were differentially expressed between healthy individuals and various cancers. Concerning circRNAs (namely, circHIPK3, circFNDC3B, and circCMTM3 derived from EVs) are upregulated and shown to regulate metatherian, tissue inhibitor of metalloproteinase 3, SOX9 through miR‐124‐3p, miR‐937‐5p, miR‐3619‐5p in breast cancer, colorectal cancer, and hepatocellular carcinoma, respectively, which enhance EC viability, migration and tube formation except in colorectal cancer to drive the process of carcinogenesis.…”
Section: Ev‐associated Ncrna‐based Regulation Of Cancer‐related Angio...mentioning
confidence: 99%
“…miRNA, which is endogenous noncoding RNA 18-22 nt in length, regulates gene expression at the posttranscriptional level by binding to the 3' untranslated region (3'UTR) region of the target gene (8). A large number of studies have shown that exosome derived miRNA regulates tumor proliferation, metastasis, and angiogenesis by silencing target genes (9,10). miR-93-5p has been noted as having a critical role in the occurrence and development of many tumors and has been associated with the clinical prognosis of patients with cancer (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%